Legal support of administrative reform - Гудима, Наталія Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article discusses the challenges of establishing and application of regulatory laws in the sphere of reforming public administration at the present stage of socio-economic development.